ANALISIS KECEPATAN DAN KELENTURAN TERHADAP KEMAMPUANDRIBBLING PEMAIN SEPAK BOLA SSB PUTRA LINTAS - Deka Ismi Mori Saputra; Ikhsan Maulana Putra (LPPM Universitas Muhammadiyah Muara Bungo, 2020)
ABSTRACT This study was based on the background of weak ball possession or the dribbling speed of the Putra Lintas soccer player so that it could not be controlled properly and the ball was released from control and made it easier for the opponent to grab the ball. In addition, players who do not have good speed appear sluggish in dribbling the ball and players who do not have good flexibility look stiff and often have collisions with opponents which cause injury to the player himself. The research method belongs to the type of research that is descriptive. Analysis using a quantitative approach aims to determine and analyze the speed and flexibility of the dribbling abilities of soccer players. The independent variable is speed (X1) and flexibility (X2), while the dependent variable is the dribbling ability of the SSB Putra Lintas Muara Bungo soccer player (Y). The results showed that speed made a significant contribution to the Dribbling Ability of SSB Putra Lintas soccer players by 42.1% .2. Then Flexibility made a significant contribution to the Dribbling Ability of SSB Putra Lintas soccer players by 16.4% .3. Speed ​​and Flexibility together provide significant contributions to Dribbling Ability by 16.1%. Key words: Analysis; Speed; Flexibility; Dribbling; Soccer